Blood pressure-lowering medication and erectile dysfunction. (June 2015) - Pucci, Mark; Patel, Rikesh
<x xml:space="preserve">Abstract</x> Summary Erectile dysfunction is very common in hypertensive men and is often attributed to blood pressure-lowering medication. Antihypertensive agents differ in their impact on erectile function. There is little good evidence. Published work suggests that angiotensin receptor antagonists and the highly selective β1-blocker nebivolol have a neutral or even beneficial effect on erectile function.